Heart breath mind : train your heart to conquer stress and achieve success - Lagos, Leah (Houghton Mifflin Harcourt, 2020)
"A scientifically proven program to alter the body's physical baseline response to stress--working specifically with heart rate-to fine-tune reflexes and perform at maximum potential"--